The Soviet Education System and the Filtering of the Jadid Heritage (1930–1941) - Nurullayev , Jasurbek (The Lingua Spectrum, 2025)
This article explores the complex interaction between the Soviet educational system in Uzbekistan and the legacy of the Jadid movement during the years 1930–1941. At the beginning of the 20th century, Jadidism, which aimed at socio-cultural and educational reform among Muslims, initially shared some similarities with the early reformist goals of the Soviet regime. However, during the 1930s, Stalin’s consolidation of power and the establishment of a rigid ideological foundation led to the systematic selection, suppression, and distortion of the Jadid heritage. Drawing on modern scholarship, particularly works by Uzbek historians, this paper analyzes the methods by which the Soviet regime marginalized Jadid ideas and figures. These methods included ideological denunciation, selective appropriation of reformist ideas (detached from their original meanings), physical persecution and elimination of Jadid intellectuals, and the creation of a new Soviet historical narrative that either erased or demonized their contributions. The study emphasizes that this filtering process played a crucial role in constructing the new Soviet Uzbek identity, but it did so at the cost of obscuring a significant part of indigenous modernist thought and blocking alternative paths of national development.